LANDSCAPE SEMIOTICS OF SUBJECTIVITY IN THE ENGLISH NOVEL OF THE 19 th CENTURY - LIVYTSKA, Inna (Linguistic and Conceptual Worldviews, 2022)
Semiotic relations between the homo sapiens and his/her topos or environment have recently become the focus of eminent or mediated fictional subjective modelling. In the course of research with the tools of the cultural discourse analysis (CDA), a range of communicative practices has been unveiled. These include among others verbalized images of the topi, descriptive outlines of the localities and directions, ways of showing, symbolic representations of typical animals, topographic lexis, verbal and non-verbal means of the visualization of the surroundings etc. The object of the research constitutes the semiotic potential of the "ethnic-physical nomenclature", which presupposes the application of the cultural discourse analysis to the environment as a form of subjectivized reality of the human being. Victorian writers provide us with the well of unlimited material in this respect as the experiencing subject of pre-industrial England has been portrayed as a sensitive agency in the imaginative fictional narrative world. Therefore, Victorian's world outlook becomes the research objective of ecocriticism, a new direction of critical discourse analysis. The aim of cultural discourse analysis in symbiosis with the ecocritical approach is to investigate ways and means of correlation of verbal and non-verbal discourses and their material and physical embodiment in culture. Ecocritical reference to the Victorian period has been considered prolific in terms of discursive means disclosing complicated relations of the approaching technological progress, great discoveries in the human physic and Nature. Positing the human being in the centre of all the animal species stressed a universal character of semiosis, where the global ecological view was put on the core of the scientific and fictional manifestation. A prominent example of this cosmological feeling is seen in a close correlation of the narratives with the setting and psychological foregrounding in the novel of George Eliot "Middlemarch", where the main character Dorothy Brooke symbolizes the Nietzschean idea of eternal return, demonstrating clear awareness of George Eliot of the evolution of species multiplied by theological subtext.
Keywords: topos, semiosphere, ethno-physical nominations, Vitorians, emotional subject, George Eliot, cultural discourse analysis (CDA)